Determination of Cyclic Load Limits for Plasma‐Sprayed Copper Tracks on Material Extrusion‐Based Printed Surfaces. Issue 7 (28th July 2022) - Stiller, Tanja; Hausberger, Andreas; Berer, Michael; Schwan, Alexander M.; Hinterer, Andreas; Spalt, Sebastian; Pinter, Gerald; Lackner, Jürgen M.
Abstract : Herein, copper particles are deposited on additively manufactured surfaces and investigations are performed to determine the mechanical properties and the impact of copper tracks on the surfaces. The basic investigation covers quasistatic tests, namely, tensile and three point bending, for three different printing orientations and two infill variations (+45°/−45° and 0°/90°), which shows no remarkable differences. In addition, a copper track is sprayed via atmospheric pressure plasma spraying (APPS) onto the polymeric samples and characterized regarding hardness and electric conductivity. Furthermore, a specific application for the copper track on the polymer substrate is recreated by a cyclic three point bending with a novel sample geometry (T‐shaped). The sprayed copper track has 60% of the hardness and 40% of the indentation modulus of bulk copper. Depending on the substrates' topography, the electric conductivity varies from 7% to 18% of bulk copper. The lifetime of the copper track (i.e., conductivity) is strongly dependent on the deformation and the fracture of the polymer underneath. The underlying failure mechanism is triggered either by the topography of the polymer substrate or as a consequence of the damage in the copper track, leading to superficial cracks in the polymer surface. Abstract : Additively manufactured components are coated with copper by atmospheric plasma spraying to produce conductive tracks on the surface. The effects on the mechanical integrity of this composite are investigated with cyclic bending. The crucial importance of surface topography and the effect of a mismatch on the mechanical properties of the copper–Ultem composite is presented.